Prognostic Value of N-Terminal Pro-B-Type Natriuretic Peptide and High-Sensitivity C-Reactive Protein in Patients With Previous Myocardial Infarction - Cao, Ye-Xuan; Li, Sha; Liu, Hui-Hui; Zhang, Meng; Guo, Yuan-Lin; Wu, Na-Qiong; Zhu, Cheng-Gang; Dong, Qian; Sun, Jing; Dou, Ke-Fei; Li, Jian-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with previous myocardial infarction (MI) have a poor prognosis and stratification for recurrent major adverse cardiovascular events (MACE) among these patients is of considerable interest. N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity C-reactive protein (hs-CRP) are considered to be potential cardiovascular risk factors, but less is known about their prognostic importance in post-MI patients. This study aimed to evaluate the prognostic value of NT-proBNP and hs-CRP alone or together in patients who reported a prior MI. Methods: In this prospective study, we consecutively enrolled 3306 post-MI patients to assess the recurrent MACE. The predictive values of NT-proBNP and hs-CRP alone and together were assessed by multivariable Cox regression using hazard ratios (HR) and 95% confidence intervals (CI). Results: During the 4-year follow-up period, 335 patients developed recurrent MACE. Multivariate Cox regression analysis showed a significant correlation between NT-proBNP levels and MACE (HR: 2.99, 95%CI: 2.06-4.36, p<0.001), hard endpoints (HR: 5.44, 95%CI: 2.99-9.90, p<0.001), cardiac mortality (HR: 5.92, 95%CI: 2.3414.96, p<0.001) and all-cause mortality (HR: 5.03, 95%CI: 2.51-10.09, p<0.001). However, hs-CRP was not an independent predictor after adjusting for NT-proBNP. When patients were divided into six groups by using tertiles values of NT-proBNP and median values of hsCRP, patients with high NT-proBNP/hs-CRP values were 3.27 times more likely to experience MACE than patients with low NT-proBNP/hs-CRP values. The addition of NT-proBNP and hs-CRP to a prognostic model revealed a significant improvement in C-statistic, net reclassification, and integrated discrimination. Conclusions: Increased NT-proBNP levels were associated with long-term worse outcomes and the combination of NT-proBNP and hs-CRP has an incremental value in the further risk stratification of post-MI patients.